Main Aspects of Peripheral and Central Hearing System Involvement in Unexplained HIV-Related Hearing Complaints - de Jong, Marrigje Aagje; Luder, Ari; Gross, Menachem (Frontiers in Neurology, 2019)
Objective: Hearing abnormalities frequently occur in Human Immunodeficiency Virus (HIV) infected individuals. Both conductive and uni- or bilateral sensorineural hearing loss (SNHL) have been described along with other audiological and vestibular symptoms such as tinnitus, vertigo and balance disturbances. While frequent middle ear infections may explain impairment of peripheral hearing abilities, the exact etiology of cochlear and central auditory processing deficits still remains unclear. Direct effects of HIV, opportunistic infections, ototoxic side effects of antiretroviral therapy (ART), and immunologic responses to the central nervous system involving the auditory pathway have been proposed. We aim to review the audiological profile in HIV infected adults related to the effects of HIV and HAART on the inner ear structures. Methods: We present a review of the literature on cases of HIV related SNHL in adult patients and studies conducted to investigate audiometric changes in such patients. Data on presentation, diagnosis and pathophysiology were reviewed. Results: Sensorineural hearing loss in the higher frequencies is a common form of hearing loss in HIV infected individuals throughout disease progression, along with decreased otoacoustic emission (OAE) responses, increased PTA hearing thresholds and prolonged latencies for auditory brainstem responses (ABR). Conclusion: HIV affects all stages of auditory perception in a way similar to accelerated aging of the auditory system. And we postulate that synaptic loss may be the first step, followed by cochlear damage and central pathology as the virus remains present in all the structures of the auditory pathway causing local inflammation and degeneration. Evaluation of hearing function among all patients diagnosed with HIV infection seems to be an accepted approach; it should include OAE testing, pure tone and speech audiometry, speech-in-noise tests and ABR measurements.